Modelling Drivers of Grievance-Fuelled Violence - Corner, Emily (Terrorism and political violence, 2025)
Acts of extreme or mass violence perpetrated by lone offenders have become increasingly common in liberal democracies over the past 20 years. Some describe these acts as ideologically motivated, while others attribute them to mental disorder or criminal intent. This has led to the development of distinct research and practice areas. However, there is an increasingly shared view that the distinction between political ideology, criminal intent and personal motivation is in fact blurred. There are an increasing number of instances where assigning an offender to a particular category has proven problematic, and this has led to an emerging consensus that the use of ideology as a marker for motivation may be flawed. This article supports an emerging area of research and argues that the motivation for the violence carried out by individuals conducting terrorism, mass murder, fixation, stalking, or familial and intimate partner homicide may be better understood through application of the concept of grievance-fueled violence. This work employs a multifaceted analytical approach to develop a holistic conceptual model of the processes of grievance development which is then tested on a sample of 120 offenders who either planned or committed an act of extreme or mass violence.